We are all in the same boat. Marina Abramović and the Barcolana - Del Marco, Vincenza (E|C, 2020)
The advertising of Barcolana50, one of the most important regattas in the world, born on the proposal of the creative director of Illycaffè, Carlo Bach, was created in February 2018 in Milan by Marina Abramović. It depicts the performer holding a white flag with the words "WE'RE ALL IN THE SAME BOAT". To be valued by some social actors such as Andrea Illy, president of Illycaffè, and Mitja Gialuz, president of the sailing company of Barcola and Grignano, is a collective message used in the context of a competition. Paolo Polidori, Northern League Deputy Mayor of Trieste, considers the advertising as political and therefore not appropriate for an event that should bring together rather than create conflicts or divide. The article proposes a reconstruction of the social discourses around the advertising, an analysis of the latter and a contextualization within the work of Marina Abramović.